The effect of nickel on the sensitivity of plasmonic photonic crystal fiber sensor - Hussein Taqi John; Imad Kamil Zayer; Ali Abed Jaber (Genius Journals, 2023)
In this work, a plasmonic optical fiber sensor is designed to sense liquid materials depending on the imaginary part of the effective refractive index responsible for the loss of these materials. This sensor consists of two groups of circles, the first group contains six holes filled for air, and the second group outer is alternately filled with the analyte and air, and this arrangement is covered with a layer of a noble metal, which is nickel, to increase the efficiency of the sensor as it produces surface plasmon resonance ( SPR ), The proposed sensor was also surrounded by a layer ( PML )to prohibit reflections in the middle of the sensor. The druid-Lorentz model was used to calculate the electrical permittivity of metals, and the Sellemier model was used to calculate the permittivity of silica
Keywords: PCF; Nobel Metals; propagation constant,; plasmonic fiber